Synthesis of 2-substituted tetraphenylenes via transition-metal-catalyzed derivatization of tetraphenylene - Pan, Shulei; Jiang, Hang; Zhang, Yanghui; Zhang, Yu; Chen, Dushen (Beilstein Journal of Organic Chemistry, 2016)
A new strategy for the synthesis of 2-substituted tetraphenylenes through a transition-metal-catalyzed derivatization has been developed. Three types of functionalities, including OAc, X (Cl, Br, I) and carbonyl, were introduced onto tetraphenylene, which allows the easy access to a variety of monosubstituted tetraphenylenes. These reactions could accelerate research on the properties and application of tetraphenylene derivatives.
Keywords: acetoxylation; carbonylation; halogenation; tetraphenylene; transition metal